Subjective well-being approach for testing money illusion evidence using data from Social Weather Stations - Beja, Edsel L. (2017)
This paper tests money illusion using measures of subjective well-being, nominal income, and price. It tests the hypothesis that there is no money illusion in the sense that proportional changes in both nominal income and price do not bring about a change in subjective well-being. The study uses food poverty data from Social Weather Stations as a proxy measure for nominal income and food Consumer Price Index inflation from the Philippine Statistics Authority as a proxy measure for price. The findings suggest no money illusion in general. More specifically, the findings provide conclusive evidence of no money illusion for the food-poor but not for the food-nonpoor.
Keywords: Money illusion; Well-being